2022
DOI: 10.3390/vaccines11010021
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Analysis of the Immunoglobulin G Response to Different COVID-19 Vaccines in Brazil

Abstract: (1) Background: COVID-19 vaccination in Brazil has been performed mostly with CoronaVac (Sinovac), ChAdOx1-S (AstraZeneca-University of Oxford) and BNT162b2 (Pfizer-BioNTech) vaccines. The titers of IgG antibodies reactive to the SARS-CoV-2 spike protein correlate with vaccine efficacy. Studies comparing vaccine immunogenicity in a real-world scenario are lacking. (2) Methods: We performed a population-based study to analyze the immunoglobulin G response to different COVID-19 vaccines. Citizens older than 18 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…In our previous studies, we demonstrated the excellent performance of the Brazilian COVID-19 vaccination program in inducing humoral immunity as measured by the levels of IgG reactive to SARS-CoV-2 Spike protein. We also reported a higher performance of the BNT162b2 vaccine (Pfizer-BioNTech) in inducing anti-Spike IgG antibodies after the initial vaccination and booster dose in comparison to other vaccines such as ChadoX and Coronavac [11], findings that have been confirmed by other studies [12][13][14].…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…In our previous studies, we demonstrated the excellent performance of the Brazilian COVID-19 vaccination program in inducing humoral immunity as measured by the levels of IgG reactive to SARS-CoV-2 Spike protein. We also reported a higher performance of the BNT162b2 vaccine (Pfizer-BioNTech) in inducing anti-Spike IgG antibodies after the initial vaccination and booster dose in comparison to other vaccines such as ChadoX and Coronavac [11], findings that have been confirmed by other studies [12][13][14].…”
Section: Introductionsupporting
confidence: 84%
“…This case study is a follow-up to a previous populational analysis of the COVID-19 antibody response [11,39]. Sampling campaigns took place between 2021 and 2022, at the Federal University of Paraná, Matinhos, Brazil.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation